PENGARUH VIRAL MARKETING DAN WORD OF MOUTH (WOM) TERHADAP KEPUTUSAN MAHASISWA MELAKUKAN PILIHAN KAMPUS - David Chandra Saputra; Mega Mirasaputri Cahyanti (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2021)
The development of the current era of globalization, the use of the internet in obtaining information is very easy. Especially during the Covid-19 Pandemic, almost all community activities are carried out online, starting from government activities, work, as well as in the world of education which is carried out online. Not left behind is also in terms of promoting the campus to the public with the internet. One of the strategies for introducing campuses to the community is viral marketing and word of mouth with internet media. This study aims to determine and explain the influence of viral marketing and word of mouth on students' decisions to make campus choices (study of 2020 students majoring in management at the Asia Malang Institute of Technology and Business). This research method using multiple linear regression method. The sampling technique in this study used non-probability sampling using the Slovin formula, the number of respondents was 155 respondents from a population of 251 people, and the data collection technique used the snow ball technique. In this study, it was found that viral marketing had a positive and significant effect on students' decisions to choose campus, and word of mouth (WOM) also had a positive and significant effect on students' decisions to make campus choices.In this study, the results showed that marketing viral had a positive and significant effect on student decisions to make campus choices, and word of mouth (WOM) also had a positive and significant effect on student decisions to make campus choices. Perkembangan era globalisasi saat ini penggunaan internet dalam memperoleh suatu informasi sangatlah mudah. Terlebih di masa Pandemi Covid-19 hampir semua kegiatan masyarakat dilakukan secara online, dimulai dari kegiatan kepemerintahan, pekerjaan, begitu juga dalam dunia pendidikan yang dilakukan secara online. Tak tertinggal juga dalam hal mempromosikan kampus ke masyarakat dengan internet. Strategi pengenalan kampus kemasyarakat salah satunya dengan viral marketing dan word of mouth dengan media internet. Penelitian ini bertujuan untuk mengetahui dan mejelaskan pengaruh viral marketing dan word of mouth terhadap keputusan mahasiswa melakukan pilihan kampus (studi pada mahasiswa angkatan 2020 jurusan manajemen institut teknologi dan bisnis asia malang). Metode penelitian ini dengan menggunakan metode regresi linier berganda. Adapun teknik pengambilan sampel dalam penelitian ini menggunakan non-probability sampling dengan menggunakan rumus slovin didapatkan jumlah responden sebanyak 155 responden dari populasi sebanyak 251 orang, serta teknik pengumpulan data menggunakan teknik snow ball. Pada penelitian ini didapatkan hasil bahwa viral marketing berpengaruh positif dan signifikan terhadap keputusan mahasiswa melakukan pilihan kampus, serta word of mouth (WOM) juga berpengaruh positif dan signifikan terhadap keputusan mahasiswa melakukan pilihan kampus